Digitalisasi Politik dalam Proses Pemilu 2024: Praktik Komodifikasi Rakyat dalam Perspektif Psikoanalisis - Solakhudin, Ahmad; Al-Hamid, Rizal (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2024)
Elections are an activity that cannot be separated from a country that adheres to a democratic system. The election is an event in the interest of occupying all lines of existing sectors. All things are legalized in elections. As a result, the meaning of humanizing humans is only limited to a concept. Elections change the perspective of something to be very important and negate the true nature of a thing. This paper discusses how the pattern of disruption of party maneuvers to get voting rights from the people by utilizing digitalization in the 2024 election. Various methods are carried out and even justified to achieve the desired thing, even though it is unforgivable. The writing method uses a literature review, and data will be obtained through literature studies from books, journals, webs, and reality related to relevant news by not leaving elements of the problem studied. The results and analysis in this paper are a benchmark for how a group can attract existing groups. As well as a follow-up on facing political contestation in the future.